Laparoscopic shaving for colorectal endometriosis: a literature review - Moukit, Mounir; Rahmoune, Mohammed; Allilou, Ismail; Babahabib, Moulay Abdellah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Colorectal endometriosis is one of the most challenging conditions to manage. Surgical treatment is required when lesions are symptomatic, impairing bowel, urinary, sexual, and reproductive functions. Preoperative radiological examination should be extensive to determine the appropriate surgery: laparoscopic shaving, disc excision or rectal resection. We demonstrated that in the hands of experienced surgeons, shaving technique is possible in more than 95% of colorectal endometriotic nodules, with low complication rates compared to resection. Shaving and bowel resection are associated with comparable recurrence rates. As shaving is indicated whatever the size of deep lesions, surgeons should first consider rectal shaving to remove deep bowel endometriosis. Bowel resection should only be performed in case of major rectal stenosis (>80%), multiple or posterior lesions and stenotic colorectal nodules.